Capability Approach to Skill: Bridging the Disciplinary Differentials over Conceptualizing Skill - Thapa, Binayak Krishna (Journal of Technical and Vocational Education and Training, 2021)
The 21st-century social science calls for trans-disciplinary perspectives. In an attempt to address this call, this paper offers a trans-disciplinary take on the concept of skill. The author delves into understanding the concept skill and explores its conceptualization across disciplines economics, sociology, and psychology. In so doing, literature review over this concept suggested that there currently exists disciplinary differentials over the concerned idea. Further, the author offers the capability approach as an alternative to understand and define skill. While skill gets explained from the economic, sociological, and psychological fields, the persistent disciplinary differentials make the conception of skill fuzzy. The author argues that the capability approach potentially bridges the disciplinary segmentation over the concept skill.